Renin-angiotensin System Blocking Antihypertensive Therapy Effect on Surrogate Glycemic and Lipid Markers in Metabolic Syndrome Patients - Zainal, Adnan A.; Chalaby, Loay A. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Metabolic syndrome (MetS) is a constellation of metabolic disorders, that together, aggravate the cardiovascular, and atherosclerotic risks. ACE inhibitors class, used for managing hypertension in MetS, induces favorable effects on glycemic control and insulin action on tissues as well as reducing all-cause mortality in HT patients. However, exploring changes associated with ACEI use and the exact impact of ACE inhibitors in hypertensive MetS patients on surrogate lipid and glycemic markers has not been reported in previous research extensively, if any. AIM: The aim of the study was to assess metabolic impact of ACE inhibition in MetS patients in terms of surrogate glucose-, insulin-, and lipid fraction-based markers. METHODS: A case–control study involving subjects diagnosed with MetS was conducted. Two study groups were involved: Hypertensive MetS patients maintained on Enalapril (n = 27), and normotensive control patients (n = 24). Triglyceride and glucose index (TyG index), triglyceride glucose-body mass index (TyG-BMI), serum insulin by TG (InsuTAG), atherogenic index of plasma (AIP), Castelli risk index-I (CRI-I) and -II (CRI-II), were calculated. RESULTS: Compared to controls, InsuTAG and TyG index were non-significantly different, AIP was significantly lower, TyG-BMI was significantly higher and CRI-I was significantly lower while CRI- II was non-significantly higher, in the treatment group. CONCLUSION: Despite controversy and scarcity of evidence in the literature, benefits of using enalapril on important components of MetS, indirectly assessed by surrogate markers, were shown in the current study and using ACE inhibitor in hypertensive MetS patients probably minimized metabolic and cardiovascular risk.